Neutrosophic soft set with application in decision making: a case study on the online food delivery service / Nurul Balqis Ramli and Siti Hajar Aisyah Mohamed Saedan - Ramli, Nurul Balqis; Mohamed Saedan, Siti Hajar Aisyah (2022)
The global market for online food delivery (OFD) has grown significantly as a result of the COVID-19 pandemic. In recent years, according to Dospinescu et al. (2020), the worldwide online food delivery market has grown at an exponential rate since consumers can order meals online and delivered to their homes on a daily basis. Extra services have proven to be useful in maintaining social distance during the COVID-19 pandemic, expanding service reach, and reducing the time and distance between sales and usage processes. In Malaysia, the online food delivery services has increase rapidly and creating a big door of opportunity for a variety of OFD platforms, as well as making it a competitive commercial sector in this country. Thus, to sustain the development and keep up with the ever-changing market dynamics, there are many measures and dimensions need to be considered by the OFD entrepreneurs. The objectives of this study are to identify the preferable of OFD companies among the UiTM Kelantan Branch students and to determine the best parameter that will influenced students to buy through OFD using neutrosophic soft set. To achieve these objectives, the neutrosophic soft set is applied to translate the linguistic evaluation statements of the experts. The parameters that being evaluated in this study are delivery cost, delivery speed, convenience of payment, web design, marketing techniques and order fulfillment. From the final result, GrabFood is the preferable OFD company as it obtained optimal decision compared to FoodPanda as the alternatives. Hence, convenience of payment is the best parameter that influenced students to buy through OFD as it has the highest weight than the other parameter